Penerapan Latihan Drill untuk Meningkatkan Kemampuan Passing pada Ekstrakulikuler Futsal - Ramadhan, Haris; Prananosa, Ahmad Gawdy; Atmanegara, Doni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effectiveness of drill training in improving passing ability in the futsal extracurricular activity at SMA Negeri 5 Lubuklinggau. The study was conducted from May 2 to June 2, 2025. The research method employed was a descriptive, quantitative approach, utilizing an experimental design with a one-group pretest-posttest design. The results showed a significant difference in passing ability using drill training in the futsal extracurricular activity at SMA Negeri 5 Lubuklinggau City. The results of the significance test between the pretest and posttest showed a t-test value of 24.004, df = 14, and a significance level of 0.05, indicating a statistically significant difference between the pretest and posttest scores. The conclusion is that drill training can improve passing ability in the futsal extracurricular activity at SMA Negeri 5 Lubuklinggau City. Keywords: Futsal, Drill Training, Passing